Relação estrutura-atividade de n-sulfonilindóis com atividade larvicida contra Aedes aegypti (Diptera: Culicidae) e toxicidade aguda em Artemia salina (Artemidae - Brito, Thaysnara Batista (2022)
Three arboviral incidents with high outbreaks of infection reported in latest years, dengue, chikungunya, Zika has been bringing significant serious consequences to the world population, and their main transmitter vector is Aedes aegypti (L.) (Diptera: Culicidae). An important challenge in the forms of control of this arthropod is in the high resistance of its population with the presence of larvicides and conventional insecticides, leading up to reduction of the effectiveness of the same. This way, the development of new larvicidal agents appears with the purpose of helping this mosquito management. Thus, this work had sought modification in the molecule of indole trough introduction of specific functional groups for the purpose of improve larvicidal activity against larvae of Ae. aegypti (target organism), as well as ascertain acute toxicity in non-target organisms (Artemia salina). Fifteen 1-(4-fluorophenyl)sulfonylindole derivatives (14.1 to 14.15) and ten N-sulfonylindoles were synthetized and tested as potential larvicidal agents against Ae. aegypti in its 3rd larval stage followed by the evaluation of the toxicity in nauplii of A. salina. Of twenty-five products obtained, twenty-three are unpublished (14.2 to 14.15 and 16.2 to 16.10) and all were analyzed by melting point, mass, infrared and nuclear magnetic resonance spectra. The efficacy of compounds was compared by the selectivity index (SI), calculated by the relationship between the LC50 values obtained in the brine shrimp toxicity tests in non-target organism and the respective LC50 of the larvicidal activity. Biological activity indicated that among the compound 1-(4- fluorophenyl)sulfonylindole (14.1 to 14.15), compound 14.1 (R=4-fluorine) exhibited largest larvicidal potency (LC50=1.49 ppm; 5.08 µM; CI=1.4-1.6 ppm), similar to the reference molecule 1-(4-fluorophenyl)sulfonylindole (7) (LC50=1.5 ppm; 5.4 µM; CI=1.3-1.7 ppm), as the respective confidence intervals (CIs) overlap. Likewise, from derivatives 16.1 to 16.10, molecule 16.1 (R=4-ehtyl) showed similar larvicidal activity (LC50=0.22 ppm; 0.77 µM; CI=0.22-0.23 ppm) when compared to its prototype compound, 1-phenylsulfonylindole (6, LC50=2.20 ppm; 0.88 µM; CI=2.03-2.45 ppm), but exhibited great larvicidal potency of all the sulfonylindoles synthesized in this study. Toxicity assays showed that the twenty-five compounds exhibited low toxicity in A. salina (LC50 above 1000 ppm) and according to the selectivity index calculations, it was observed that 16.1 molecule exhibited the higest SI (>4545), proving to be above 4545 times more selective to Ae. aegypti and less toxic to A. salina. Relationships between structural changes sulfonylindoles derivatives obtained and their results of LC50 indicated influence of introduction of fluorine and groups wuth low molar volume at C-4 and C-7 of indole ring and C-4 of the benzenosulfonic ring on the larvicidal activity against Ae. aegypti. In view of this context, it was possible to provide useful information on Structure-Activity Relationship (SAR) for understanding the influence of physicochemical properties on larvicidal and toxic action in non-target organisms o these groups of compounds, which can assistant in the development of more larvicidal activities